2015
DOI: 10.1016/j.joa.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Translation and validation of the Malay version of the Stroke Knowledge Test

Abstract: BackgroundTo date, there is a lack of published studies on assessment tools to evaluate the effectiveness of stroke education programs.MethodsThis study developed and validated the Malay language version of the Stroke Knowledge Test research instrument. This study involved translation, validity, and reliability phases. The instrument underwent backward and forward translation of the English version into the Malay language. Nine experts reviewed the content for consistency, clarity, difficulty, and suitability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 14 publications
1
44
2
Order By: Relevance
“…This revealed that the stroke patients had some awareness on the disease process. The understanding of disease process will help them to appreciate the difference between stroke and heart attack that is commonly confused by most people (Nguyen TT et al 2009,Sullivan KA and Waugh D. 2005, Sowtali SN. 2015, Jones SP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This revealed that the stroke patients had some awareness on the disease process. The understanding of disease process will help them to appreciate the difference between stroke and heart attack that is commonly confused by most people (Nguyen TT et al 2009,Sullivan KA and Waugh D. 2005, Sowtali SN. 2015, Jones SP.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly held misconceptions were indicated when 25% or more of stroke patients endorsed an incorrect response option (Sullivan K and Dunton NJ 2004, Sullivan KA and Waugh D 2005, Sowtali SN 2015. This shows that the stroke patients might have wrong concept regarding stroke disease or had made a choice by guessing.…”
Section: Common Misconceptions Regarding Stroke Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…We received the “permission to use” from the authors of the original (English) and the translated (Malay language) versions of the questionnaires, deemed to be locally appropriate for this study [ 42 - 45 ]. The researchers also conducted a face and content validity analysis with 5 patients and experts prior to this study to confirm the understandability and the content validity index>0.80 of MUSE, BMQ-specific, and BIPQ for the named medication(s), for which the word “illness” was replaced with “stroke” in the measures.…”
Section: Methodsmentioning
confidence: 99%